Compression of cognitive morbidity by higher education in individuals aged 75+ living in Germany. (19th July 2018) - Rodriguez, Francisca S.; Matschinger, Herbert; Angermeyer, Matthias C.; Luck, Tobias; Riedel‐Heller, Steffi G.
Abstract : Background: Previous studies have shown that higher education may reduce dementia risk and promote a better cognitive functioning in older age. Objective: The study investigated to what extent higher education leads to compression of cognitive morbidity, and thus a shorter lifetime affected by cognitive impairment and dementia, in individuals aged 75 years and older living in Germany. Methods: Our sample included n  = 742 individuals of the population‐based Leipzig Longitudinal Study of the Aged (LEILA75+; 1998‐2013), who were free of dementia at baseline. The impact of higher education on compression of cognitive morbidity was studied by analyzing the association between education and (1) cognitive functioning over the study period and age at dementia onset, (2) age at death, and (3) the cumulative lifetime cognitive morbidity. Results: Individuals with more years of education had a higher cumulative cognitive functioning over the lifetime period 75 to 100 years (weighted for survival probability), but not a later age of dementia onset nor a later age at death. Conclusion: Our results suggest, in individuals aged 75 years and older, higher education only compresses cognitive morbidity prior to dementia onset. Findings may be specific to countries where education is not a necessary requirement for access to good quality health care services.